Assessing colitis ex vivo using optical coherence elastography in a murine model - Nair, Achuth; Liu, Chih Hao; Singh, Manmohan; Das, Susobhan; Le, Triet; Du, Yong; Soomro, Sanam; Aglyamov, Salavat; Mohan, Chandra; Larin, Kirill V. (Quantitative Imaging in Medicine and Surgery, 2019)
Background: Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) that causes regions of ulceration within the interior of the colon. UC is estimated to afflict hundreds of thousands of people in the United States alone. In addition to traditional colonoscopy, ultrasonic techniques can detect colitis, but have limited spatial resolution, which frequently results in underdiagnoses. Nevertheless, clinical diagnosis of colitis is still generally performed via colonoscopy. Optical techniques such as confocal microscopy and optical coherence tomography (OCT) have been proposed to detect UC with higher resolution. However, UC can potentially alter tissue biomechanical properties, providing additional contrast for earlier and potentially more accurate detection. Although clinically available elastography techniques have been immensely useful, they do not have the resolution for imaging small tissues, such as in small mammalian disease models. However, OCT-based elastography, optical coherence elastography (OCE), is well-suited for imaging the biomechanical properties of small mammal colon tissue. Methods: In this work, we induced elastic waves in ex vivo mouse colon tissue using a focused air-pulse. The elastic waves were detected using a phase-stabilized swept source OCE system, and the wave velocity was translated into stiffness. Measurements were taken at six positions for each sample to assess regional sample elasticity. Additional contrast between the control and diseased tissue was detected by analyzing the dispersion of the elastic wave and tissue optical properties obtained from the OCT structural image. Results: The results show distinct differences (P